2020
DOI: 10.1039/d0na00312c
|View full text |Cite
|
Sign up to set email alerts
|

Core–shell Au@AuAg nano-peanuts for the catalytic reduction of 4-nitrophenol: critical role of hollow interior and broken shell structure

Abstract: Bimetallic hollow core-shell nanoparticles have gained immense attention especially, as a high-performance catalyst due to their large surface area and increased number of uncoordinated atoms. But, the synthesis of anisotropic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 63 publications
2
3
0
Order By: Relevance
“…The overall peanut shape indicates a preferential growth from the corner {111} facets of the nanorods, as seen from the increase in dimension of the corner facets. On the other hand, the {100} facets present in the side and tip remain preserved . The blue shift of the LSPR wavelengths of the Au-PNS structure is consistent with an overall decrease of the aspect ratio from 3.15 (for AuNR) to 2.23 (for Au-PNS).…”
Section: Results and Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The overall peanut shape indicates a preferential growth from the corner {111} facets of the nanorods, as seen from the increase in dimension of the corner facets. On the other hand, the {100} facets present in the side and tip remain preserved . The blue shift of the LSPR wavelengths of the Au-PNS structure is consistent with an overall decrease of the aspect ratio from 3.15 (for AuNR) to 2.23 (for Au-PNS).…”
Section: Results and Discussionsupporting
confidence: 74%
“…On the other hand, the {100} facets present in the side and tip remain preserved. 15 The blue shift of the LSPR wavelengths of the Au-PNS structure is consistent with an overall decrease of the aspect ratio from 3.15 (for AuNR) to 2.23 (for Au-PNS). Typically, the TSPR of gold nanorods is observed between 500 and 530 nm.…”
Section: ■ Results and Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The yolk–shell structures not only exhibit a substantial surface area, but also possess porosity that enables the entrapment of reactant molecules within their cavities, thereby augmenting the rate of the catalytic reaction. 30 It has been demonstrated that the catalytic reaction occurs within the confines of the hollow nanoparticles (NPs), resulting in an increased reaction rate inside the cavity. 31 In addition, compared with the hollow-structure, the movable core of yolk–shell structures can prevent the active metal within the cavity from migrating and agglomerating.…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting that the catalytic activity of the Au core NPs is influenced by not only the Ag shell but also the same Au shell. The optical and catalytic studies of monolayer shell on Au core (Au@Ag), alloy shell on Au core (Au@AgAu), and multi‐shells on Au core (Au@Ag@Au@Ag) have also been reported [23–27] . However, systematic and detailed analysis of the optical and catalytic properties of various shell layers (such as monolayer shell (MLS), bilayer shell (BLS), and alloy layer shell (AS) on core NPs) are not reported.…”
Section: Introductionmentioning
confidence: 99%